2019
DOI: 10.1042/bsr20190513
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms of Robo4 and their effects on angiogenesis

Abstract: Roundabout4 (Robo4) is a transmembrane receptor that belongs to the Roundabout (Robo) family of axon guidance molecules. Robo4 is an endothelial-specific receptor that participates in endothelial cell migration, proliferation, and angiogenesis and the maintenance of vasculature homeostasis. The purpose of this review is to summarize and analyze three main mechanisms related to the expression and function of Robo4 during developmental and pathological angiogenesis. In this review, static shear stress and the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 140 publications
3
36
0
Order By: Relevance
“…2 A , Left ). It has been demonstrated that the soluble ligand Slit2, by interacting with Robo4, can modulate endothelial permeability and integrity in the lungs ( 25 ). Therefore, we administered Slit2 daily intravenously (i.v.)…”
Section: Resultsmentioning
confidence: 99%
“…2 A , Left ). It has been demonstrated that the soluble ligand Slit2, by interacting with Robo4, can modulate endothelial permeability and integrity in the lungs ( 25 ). Therefore, we administered Slit2 daily intravenously (i.v.)…”
Section: Resultsmentioning
confidence: 99%
“…To date, several downstream signals of the Robo receptor have been identified ( Ypsilanti et al, 2010 ; Blockus and Chédotal, 2016 ; Dai et al, 2019 ; Jiang et al, 2019 ; Tong et al, 2019 ). Here, we focus on two Slit-Robo-mediated signal transduction systems that are involved in cerebral cortex formation.…”
Section: Molecular Pathway Of Slit-robo Signalingmentioning
confidence: 99%
“…Other pathways regulating microvascular function, such as Slit-2/Roundabout (Robo4), may also be involved in the pathobiology of SM. Robo4 is expressed by endothelial cells, and when activated via Slit-2, it promotes endothelial quiescence by blocking Srcmediated VE-cadherin internalization, a key component of adherens junctions [81][82][83]. Consistent with this role, lower Slit-2 expression is associated with microvascular dysfunction and severe infections [83,84].…”
Section: Endothelial Activationmentioning
confidence: 89%